Pigeon Pea Leaves 1 - Rinderpest 0 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Will the final whistle soon blow on rinderpest, one of the oldest known diseases of livestock?